Identification and characterization of the pathogenic potential of phenol-soluble modulin toxins in the mouse commensal Staphylococcus xylosus - Reshamwala, Kunal; Cheung, Gordon Y. C.; Hsieh, Roger C.; Liu, Ryan; Joo, Hwang-Soo; Zheng, Yue; Bae, Justin S.; Nguyen, Thuan H.; Villaruz, Amer E.; Gozalo, Alfonso S.; Elkins, William R.; Otto, Michael (Frontiers in Immunology, 2022)
In contrast to the virulent human skin commensal Staphylococcus aureus, which secretes a plethora of toxins, other staphylococci have much reduced virulence. In these species, commonly the only toxins are those of the phenol-soluble modulin (PSM) family. PSMs are species-specific and have only been characterized in a limited number of species. S. xylosus is a usually innocuous commensal on the skin of mice and other mammals. Prompted by reports on the involvement of PSMs in atopic dermatitis (AD) and the isolation of S. xylosus from mice with AD-like symptoms, we here identified and characterized PSMs of S. xylosus with a focus on a potential involvement in AD phenotypes. We found that most clinical S. xylosus strains produce two PSMs, one of the shorter alpha- and one of the longer beta-type, which were responsible for almost the entire lytic and pro-inflammatory capacities of S. xylosus. Importantly, PSMalpha of S. xylosus caused lysis and degranulation of mast cells at degrees higher than that of S. aureus delta-toxin, the main PSM previously associated with AD. However, S. xylosus did not produce significant AD symptoms in wild-type mice as opposed to S. aureus, indicating that promotion of AD by S. xylosus likely requires a predisposed host. Our study indicates that non-specific cytolytic potency rather than specific interaction underlies PSM-mediated mast cell degranulation and suggest that the previously reported exceptional potency of delta-toxin of S. aureus is due to its high-level production. Furthermore, they suggest that species that produce cytolytic PSMs, such as S. xylosus, all have the capacity to promote AD, but a high combined level of PSM cytolytic potency is required to cause AD in a non-predisposed host.